Autocatalysis and CO2: Carbon Capture and Utilization (CCU) Meets Natural Processes - Gastelu, Gabriela (2023)
Autocatalytic reactions were proposed to play a key role at the beginning of life starting from the first reduction of CO2 to formate, acetate and C1 C4 hydrocarbons. In carbon capture and utilization (CCU) processes, the same reactions were demonstrated to be autocatalytic and, in some cases, promoted by catalysts of the same composition. Through evolution, CO2 reduction then turned into complex autocatalytic networks such as photosynthesis, where CCU chemists found inspiration for the development of more advanced systems for the synthesis of value-added chemicals. Less evolved systems than photosynthesis, however, may be easier to emulate and provide valuable inspiration into CO2 reduction chemistry for CCU. Other synthetic systems were also demonstrated to be autocatalytic demonstrating that CO2 reactions and autocatalysis are closely connected. In this concept article, the relationship between natural, artificial and bio-inspired autocatalytic CO2 reduction processes is summarized and discussed. The accomplishments resulting from the integration of autocatalysis and CCU strategies, along with their inherent benefits and future prospectives are also outlined.